Redistributive outcome of sickness insurance: An empirical study of social insurance institutions - Jahangir Khan; Bjarne Jansson (Luxembourg Income Study (LIS), 2006)
Aims: We analyzed the redistributive outcomes for sickness benefits using a typology of social insurance institutions compared to external factors for sickness risk. Material: Unbalanced panel data of the Luxembourg Income Study on household earnings, sickness benefits and labour force demography (OECD data) and educational attainment were employed. Method: Gini-coefficients were used for measuring earnings inequality. Relative changes in earnings inequality for sickness benefits were explained by social insurance institutional dummies using multiple regression analyses. Demography and education were included in an extended model. Results: The typology explained the redistributive outcomes as expected. When adding external variables, the observed pattern of the typology could not be repeated. Conclusions: Our results indicate that the demographic structure and educational attainment have a stronger influence on the redistributive outcome of sickness benefits than the established social insurance typology.
Keywords: 330; earnings; inequality; sickness benefits; social security; typology; Verteilungswirkung; Krankenversicherung; Einkommenseffekt; Soziale Sicherheit; Schätzung; Europa